(untitled) (Italian Journal of Public Health, 2008)
The interest in measuring the health of populations, through measuring the demand and offers of health care, is deeply rooted in history. Population health indicators in use today are built upon from mortality measures from the 1500s; regular census information starting from the 1800s; civil registration records of vital statistics commencing in the 1850s; regular national surveys, which were first initiated in the 1950s; and health system and other administrative databases used widely since the 1960s. The ancient Greeks believed that the God of medicine had two daughters: Hygeia and Panacea, the first was the goddess of prevention and wellness, while the second was the goddess of treatment. Thus suggesting that people have long believed that there is more to health than health care. Today the actual concept of population health recognizes many interconnected aspects of society, the environment, and individuals all contributing to health. To increase opportunities for comparability, more valid, comprehensive and standardized ways of measuring and reporting on population health indicators are needed. The use of health indicators contributes to overall population health goals, namely improving the health populations, reducing health inequalities and measuring the performance of health care system. The objective of performance assessment is to provide governments and populations with information about the state of their health care system.